Komite Audit, Kualitas Audit dan Manajemen Laba (Studi Empiris Pada Perusahaan Non-Finansial Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017) - Tori Agustrin; Adi Firman Ramadhan (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
Interaction between various internal and external corporate governance mechanism in reducing earning management must be analyzed deeply. Based on this case, this study aims to analyze the effect of the effective audit committee and the interaction between the audit committee with the qualified external auditor in reducing earning management. Audit committee is measured by forming a score from the number of members formed an audit committee and the number of audit committee’s meetings in one year, while audit quality from external auditor is measured based on the auditor’s industry specialization, auditor’s reputation and audit tenure. The sample of this study was obtained through purposive sampling method so that 93 samples of non-financial company in Indonesia was obtained. A linear-multiple regression analysis was used to test the hypothesis of this study. The result of this study indicate that the audit committee has a negative effect on earning management, the interaction between the audit committee and industry specialist auditor has no effect on earning management, the interaction between the audit committee and Big Four auditor has a negative effect on earning management and the interaction between the audit committee and auditor tenure has no effect on earning management.